2016
DOI: 10.1136/emermed-2015-205211
|View full text |Cite
|
Sign up to set email alerts
|

The transition to clinical expert: enhanced decision making for children aged less than 5 years attending the paediatric ED with acute respiratory conditions

Abstract: BackgroundRates of unplanned paediatric admissions are persistently high. Many admissions are short-stay events, lasting less than 48 hours.ObjectiveThis qualitative research explores factors that influence clinical decision making in the paediatric ED (PED) for children under 5 attending with acute respiratory conditions, focusing on how management decisions adapt with increasing experience.MethodSemi-structured interviews were conducted with 15 PED clinicians (doctors, emergency nurse practitioners and regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 19 publications
(20 reference statements)
0
17
0
Order By: Relevance
“…Teachers responded intuitively to meet the individual needs of the child. Intuition is an important part of professional decision-making which arises from an accumulation of experience [ 37 ]. Teachers described using strategies that were consistent with evidence-based management approaches for CFS/ME and chronic health conditions more generally.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers responded intuitively to meet the individual needs of the child. Intuition is an important part of professional decision-making which arises from an accumulation of experience [ 37 ]. Teachers described using strategies that were consistent with evidence-based management approaches for CFS/ME and chronic health conditions more generally.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing levels of tacit knowledge seem to promote intuitive judgements and data-driven rules of thumb. 7–10 …”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, however, that in creating these guidelines, when the evidence for the guidance is lacking, consensus is employed. In addition, guidelines are intended to be assistive, rather than directive, and therefore clinicians often operate outside the guidance in line with their clinical experience, e.g., it has been shown that junior doctors are more likely to use guidelines rigidly than more senior doctors, who tend to go on clinical intuition [ 12 ]. In practice, chest radiographs are performed frequently for suspected pneumonia in children [ 5 ].…”
Section: Introductionmentioning
confidence: 99%